Analisis Perencanaan Penambahan Pembangkit Tegangan Menengah di PT XYZ - Chanysia Feychin Romani; I Made Aris Sastrawan (Study Program of Industrial Engineering, Udayana University, 2025)
The availability of a reliable and sufficient electricity supply is a crucial factor in supporting economic growth and societal activities. PT XYZ, as the state-owned company responsible for electricity generation and distribution in Indonesia, faced challenges in maintaining the balance between electricity supply and demand, including in the Bali region. As electricity consumption continued to increase, proper planning was required for managing the power system, particularly in the medium-voltage subsystem. This study aimed to forecast the peak load for the year 2025 and analyze the need for additional generation capacity in the Bali Subsystem. The method employed was Double Exponential Smoothing (DES), with parameter optimization for α and β using the Solver feature in Microsoft Excel to enhance forecasting accuracy. The data used consisted of monthly peak load values from 2024. The forecasting results indicated that the Solver method produced a peak load estimate of 1,287 MW with a MAPE value of 1.50%, which was more accurate than the initial DES method that yielded a MAPE of 5.91%. Meanwhile, the current generation capacity of 1,388 MW leaves only a 101 MW reserve margin, which is below the minimum safety threshold of 130 MW. This condition highlighted the importance of adding medium-voltage generation capacity to maintain the reliability of the Bali power system in the face of potential disturbances and future demand increases.